1999
DOI: 10.1093/jac/43.5.675
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the toxicity of fluconazole and other azole antifungal drugs to murine and human granulocyte -macrophage progenitor cells in vitro

Abstract: We studied the inhibitory effects on colony formation by granulocyte-macrophage colony forming units (cfu-gm) of eight azole antifungal agents in vitro. All agents, except fluconazole, inhibited colony formation dose-dependently with 50% inhibitory concentrations (IC50) in the range of 0.78-49 micromol/L in cultures of murine and human bone marrow. For human cells, the IC50 values were 0.553 mg/L for itraconazole, 1.24 mg/L for saperconazole, 2.58 mg/L for clotrimazole, 5.33 mg/L for miconazole, 6.17 mg/L for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 20 publications
3
17
0
Order By: Relevance
“…In a primary rat hepatocyte culture system allowing the assessment of plasma membrane integrity and mitochondrial as well as lysosomal stability fluconazole was shown to exert considerably less cytotoxic effects than ketoconazole (17). Similar results were also seen in human granulocyte-macrophage progenitor cells in vitro (18).…”
Section: Discussionsupporting
confidence: 56%
“…In a primary rat hepatocyte culture system allowing the assessment of plasma membrane integrity and mitochondrial as well as lysosomal stability fluconazole was shown to exert considerably less cytotoxic effects than ketoconazole (17). Similar results were also seen in human granulocyte-macrophage progenitor cells in vitro (18).…”
Section: Discussionsupporting
confidence: 56%
“…This may point to fluconazole's greater toxicity. Fluconazole is known to lower the expression of various cytokine genes because of its lipophilic character (17). The increased glomerular diameter and volume in the fluconazole group seem to confirm the migration of neutrophils (18).…”
Section: Resultsmentioning
confidence: 88%
“…The MIC 90 was 0.12 µg/ml, whereas the minimum bactericidal concentration was 0.125 µg/ml for both drugs, demonstrating their excellent bactericidal activities [81]. Ex vivo studies on mice splenocytes following exposure to clotrimazole and econazole confirmed the good tolerance and synergistic effects of these drug [82]. Further in vivo analyses have determined that econazole is well tolerated in combination therapies and equipotent to RIF in the treatment of murine TB [83].…”
Section: Azolesmentioning
confidence: 86%